2021
DOI: 10.3389/fphar.2021.720387
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Ameliorates Diabetic Renal Tubulointerstitial Fibrosis by Restoring Autophagy via Regulation of the miR-192-5p/GLP-1R Pathway

Abstract: Tubulointerstitial fibrosis is one of the most common pathological features of diabetic nephropathy. Autophagy, an intracellular mechanism to remove damaged or dysfunctional cell parts and maintain metabolic homeostasis, is inhibited in diabetic neuropathy. Icariin is a traditional Chinese medicine extract known for nourishing the kidney and reinforcing Yang. In this study, we investigated the effects and mechanism of Icariin on renal function, autophagy, and fibrosis in type 2 diabetic nephropathic rats and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 69 publications
(82 reference statements)
2
13
0
Order By: Relevance
“…Another studied flavonoid is Icariin, found in Epimedium plant species. It possesses many biological roles, while in DKD, it shows an anti-fibrotic and antioxidant effect, the last one in an NRF2 partially dependent pathway [ 165 , 166 ]. Other representatives that can trigger the NRF2/KEAP1/ARE pathway are Diphlorethohydroxycarmalol, derived from Ishige okamurae, a species of algae [ 167 ], Genistein [ 6 ], Hesperetin [ 168 ], Myricetin [ 169 ] and Digitoflavone (3,0,4,5,7-tetrahydroxyflavone) [ 170 , 171 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
“…Another studied flavonoid is Icariin, found in Epimedium plant species. It possesses many biological roles, while in DKD, it shows an anti-fibrotic and antioxidant effect, the last one in an NRF2 partially dependent pathway [ 165 , 166 ]. Other representatives that can trigger the NRF2/KEAP1/ARE pathway are Diphlorethohydroxycarmalol, derived from Ishige okamurae, a species of algae [ 167 ], Genistein [ 6 ], Hesperetin [ 168 ], Myricetin [ 169 ] and Digitoflavone (3,0,4,5,7-tetrahydroxyflavone) [ 170 , 171 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
“…Jia et al found that icariin can induce autophagy and reduce renal fibrosis in the DKD models, and its mechanism is related to the reduction of miR-192-5p, its overexpression inhibited glucagon-like peptide 1 receptor (GLP-1R), induced p-mTOR expression, and increasing the expression of collagen I, α-SMA, and FN. Icariin can alleviate DKD renal fibrosis by restoring autophagy through the miR-192-5p/GLP-1R pathway [ 137 ]. In addition, Zang et al found that miR-122-5p also plays a role in the development of DKD, miR-122-5p inhibited forkhead box protein P2 (FOXP2) transcription, resulting in decreased cell viability, and inhibit E-cadherin expression, increasing α-SMA expression.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Cyclocarya paliurus triterpenic acids or reduced expression of thioredoxin interacting protein (TXNIP) acted through mTOR or in combination with the AMPK pathway to induce autophagy ( Huang et al, 2016 ; Zhang et al, 2019 ). In contrast, the Chinese herbal extract icariin from Epimedium restored autophagy and attenuated renal tubulointerstitial fibrosis by targeting miR-192-5p/GLP-1R (GLP-1 receptor) in a DKD model ( Jia et al, 2021 ). At the same time, the overexpression of TXNIP (one of the factors of autophagy) induced by high glucose led to autophagy dysfunction and participated in the occurrence of DKD ( Huang et al, 2014 ).…”
Section: Dkd and Autophagymentioning
confidence: 99%